Comparing care at walk-in centres and at accident and emergency departments: an exploration of patient choice, preference and satisfaction. Issue 4 (23rd March 2007) - Chalder, Melanie; Montgomery, Alan; Hollinghurst, Sandra; Cooke, Matthew; Munro, James; Lattimer, Val; Sharp, Deborah; Salisbury, Chris
Abstract : Objectives: To explore the impact of establishing walk-in centres alongside emergency departments on patient choice, preference and satisfaction. Methods: A controlled, mixed-method study comparing 8 emergency departments with co-located walk-in centres with the same number of "traditional" emergency departments. This paper focuses on the results of a cross-sectional questionnaire survey of users. Results: Survey data demonstrated that patients were frequently unable to distinguish between being treated at a walk-in centre or at an accident and emergency (A&E) department and, even where this was the case, opportunities to exercise choice about their preferred care provider were often limited. Few made an active choice to attend a co-located walk-in centre. Patients attending walk-in centres were just as likely to be satisfied overall with the care they received as their counterparts who were treated in the co-located A&E facility, although walk-in centre users reported greater satisfaction with some specific aspects of their care and consultation. Conclusions: Whereas one of the key policy goals underpinning the co-location of walk-in centres next to an A&E department was to provide patients with more options for accessing healthcare and greater choice, leading in turn to increased satisfaction, this evaluation was able to provide little evidence to support this. The high percentage of patients expressing a preference for care in an established emergency department compared with that in a new walk-in centre facility raises questions for future policy development. Further consideration should therefore be given to the role that A&E-focused walk-in centres play in the Department of Health's current policy agenda, as far as patient choice is concerned.